Experimental Investigation of the Propagation and Attenuation Rule of Blasting Vibration Wave Parameters Based on the Damage Accumulation Effect - Huaibao Chu; Xiaolin Yang; Shuanjie Li; Weimin Liang (Shock and Vibration)
The propagation and attenuation rule of blasting vibration wave parameters is the most important foundation of blasting vibration prediction and control. In this work, we pay more attention to the influence of the damage accumulation effect on the propagation and attenuation rule of vibration wave parameters. A blasting damage accumulation experiment was carried out, the ultrasonic wave velocity of the specimens was measured, and the damage value was calculated during the experiment. The blasting vibration wave was monitored on the surface of the specimens, and its energy was calculated by using the sym8 wavelet basis function. The experimental results showed that with the increase in the number of blasts, the damage continues to increase; however, the vibration velocity and the main frequency decrease continuously, the unfocused vibration wave energy in the zone near to the blasting source is rapidly concentrated in the low-frequency band (frequency bands 1 to 3), and the energy is further concentrated in the low-frequency band in the intermediate zone and zone far from the blasting source. There is a distortion process in which the vibration velocity and the main frequency increase slightly and the energy of the blasting vibration wave converges to the high-frequency band (the 5th band) before the sudden unstable fracture failure of the specimens. The experimental results indicate that the prediction and evaluation of blasting vibration should consider the variation rule of blasting vibration wave parameters synthetically based on the cumulative damage effect, and it is not safe to use only one fixed vibration control standard for the whole blasting operation.